Exploring Family Communication and Behavior with The Sakinah Family During The Covid-19 Period - Ahmad Fauzan; Muhammad Zakir Husein; Ahmad Ahmad; Eka Sufartianinsih Jafar (Al-'Adl, 2022)
Communication and behavior are the main components that still need to be considered to see the level of family harmony during Covid-19, most of which are designing the effects of the pandemic giving birth to domestic violence and divorce. The purpose of this study was to complement and review the existence of the family in aspects of communication and behavior in the family environment during the pandemic in realizing a sakinah family. The research design tends to be phenomenal with a social communication approach. Data collection was done by direct interview. The results of this study show, first, that interpersonal and multipersonal family communication and behavior are positive so that the pressure of the Covid-19 pandemic is not too significant on the level of violence and divorce. Second, the supporting factors in family communication and behavior are the existence of routine religious social activities, demographic conditions, and openness to the social and family environment, especially different religions, ethnicities and races.